Acceptance and Development of Covered Open Firing in Yayoi Pottery - Nagatomo, Tomoko (Nihon Kokogaku(Journal of the Japanese Archaeological Association), 2006)
It is shown clearly in former research that the method of covered open firing pottery production using rice-straw was introduced with the full-scale introduction of wet-field rice agriculture in the Yayoi period. This pottery firing method was excellent in that earthenware could be heated in the circumference of the fire, stably raising temperature over many hours, different from the open firing without covering of the Jomon culture. Further, covered open firing is well adapted with the environment reclaimed by paddy field development. The question becomes, how was this firing method received and developed on the islands where paddy fields were being established? This paper considered such a subject by examining data centering on the western part of Japan. Specifically, by observing the smoke that adheres at the time of pottery firing, the author made clear the situations of the pottery circumference, such as fuel at the firing time according to the form of the smoke, and estimated how pottery was placed from the existence and the position of the smoke. When examined from such a viewpoint, the following results emerge. (1) The similarity of changes of firewood fuel in the western part of Japan shows similarity in the relationship between humans and the environment, at least in the western part of Japan. (2) Regionality becomes most evident through pottery kiln insertion angle in the middle of the Yayoi period. (3) Pottery kiln insertion angle at the firing time was continuous from the late stage to the terminal stage of the Yayoi period in the Okayama Plain. But, in the Osaka coastal area, traditional pots that continued from the late stage of the Yayoi period were inserted differently from the thin Shonai type pot and thin Furu type pot. Therefore, it is possible that there was a difference in the places of production between traditional pots and thin Shonai type pots and thin Furu type pots. (4) Piled up baking starts from late stages of Yayoi. In spite of the simplicity, this is a sign that efforts to increase pottery production efficiency were accepted. And it is thought that such changes were caused not only from changes of the firing method, but also from a change in pottery manufacture from a technology based on clay coiling to a process of drying pottery through a process of adjustment and ornamentation.